Landscape and phytocenotic representativeness of regional econet of Gerkasy region in the Leftbank Dnieper - Конякін, С. М.; Чемерис, І. А. (Man and Environment. Issues of Neoecology, 2014)
The article analyzes the natural resource potential as a major component of the regional ecological network of Cherkasy region within the left-bank Dnieper. The assessment of protected areas on landscape and phytocenotic indicators was carried out for determining the structural elements of the region’s ecological network research. With a view to the effective functioning of ecological network the set of geo-ecological threats and ways of their optimal solutions was defined. There was created geographical model of Cherkasy region Econet which is based on above-ground and aquatic landscape complexes.